Transport Activity Measurement Toolkit for On-Road Vehicles : Practitioners' Guide - Rogers, John A. (World Bank, Washington, DC, 2014)
Although urbanization is frequently cited as a major cause of greenhouse gas and local air pollution emissions growth, it could be better understood as one of the crucial links between climate and development. Urbanization is a major driver of development, and once in cities, people tend to increase their mobility dramatically, driving an increase in greenhouse gas and other emissions from transport. The demand for transport is not limited only to urban environments. As each economy becomes richer, its demand for passenger and freight mobility increases. This increase in car usage coupled with a tendency to have a lower number of passengers per car, has been sufficient to offset the improvements gained in vehicle fuel efficiency. The increasing transport demand, if not accompanied by adequate growth in infrastructure and facilities, leads to rising congestion, time loss, and air quality deterioration that can stifle economic growth and quality of life. Finding the delicate balance of policy options to achieve long-term improvements in on-road transport and reduce the impact of its externalities is critical and needs to be tailored to each locale. This requires measurements both to design the interventions and evaluate their impacts. This transport activity measurement toolkit (TAMT) has been developed specifically to simplify this measurement process by providing standardized software, data collection forms, and a consistent standardized methodology.